2019
DOI: 10.1002/hed.25744
|View full text |Cite
|
Sign up to set email alerts
|

The change in circulating tumor cells before and during concurrent chemoradiotherapy is associated with survival in patients with locally advanced head and neck cancer

Abstract: Background This study aimed to evaluate the role of baseline circulating tumor cells (CTCs) before and during concurrent chemoradiotherapy and attempted to determine the impacts of CTCs on the outcomes in patients with head and neck squamous cell carcinoma. Methods CTCs were detected using a negative selection strategy and flow cytometry protocol. Results We observed a significant correlation between baseline CTCs and staging (P = 0.001). The CTC counts were significantly reduced within 2‐4 weeks in 47 concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…The results of the present study are in accordance with other studies investigating CTCs in solid cancers, including the head and neck, which revealed that the presence of CTCs may influence prognosis (11)(12)(13)(14)(15)(16)(17)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) similar to what was observed in the patients in the present study (6/8 were positive to CTC preoperatively). A recent meta-analysis comprised of 17 studies confirmed the significant prognostic value of CTCs in patients with head and neck cancer, wherein positive CTCs were significantly associated with poor overall, disease-free and progression-free survival (61).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study are in accordance with other studies investigating CTCs in solid cancers, including the head and neck, which revealed that the presence of CTCs may influence prognosis (11)(12)(13)(14)(15)(16)(17)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) similar to what was observed in the patients in the present study (6/8 were positive to CTC preoperatively). A recent meta-analysis comprised of 17 studies confirmed the significant prognostic value of CTCs in patients with head and neck cancer, wherein positive CTCs were significantly associated with poor overall, disease-free and progression-free survival (61).…”
Section: Discussionsupporting
confidence: 92%
“…In a combined study for metastatic breast and prostate cancer, Coumans et al demonstrated that for initially CTC-positive patients, a decrease of CTC count below the cut-off after 6-8 weeks of therapy is the best indicator of treatment response [38]. The association of therapy response and conversion from positive to negative CTC status was also demonstrated for metastatic non-small cell lung cancer, locally advanced head and neck cancer and gastric cancer [39][40][41]. Lorente et al described a 30% CTC decline 4 weeks after treatment for castration-resistant prostate cancer with initially ≥5 CTCs/7.5 mL as independently associated with OS and a more sensitive biomarker than 50% CTC decline [27].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, markers from liquid biopsies that are directly related to cancer cells or cancer‐produced molecules have been employed, including circulating tumor cells (CTCs), cell‐free DNA (cfDNA)/circulating tumor DNA (ctDNA), cfRNA, and exosomes . It is generally accepted that CTCs may play an important role in cancer metastasis .…”
Section: Biomarkers From Liquid Biopsiesmentioning
confidence: 99%
“…188 However, some are not always cancer-specific, giving rise to problems in distinguishing between malignant and inflammatory disease. [189][190][191][192] More recently, markers from liquid biopsies that are directly related to cancer cells or cancer-produced molecules have been employed, including circulating tumor cells (CTCs), 147,[150][151][152][153][154][155][156][157][158][159][160][161][162][163][164]193,194 cell-free DNA (cfDNA)/ circulating tumor DNA (ctDNA), [187][188][189][190][191][192]195,196 cfRNA, 184 and exosomes. [196][197][198] It is generally accepted that CTCs may play an important role in cancer metastasis.…”
Section: Biomarkers From Liquid Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation